Voting in Union Certification Elections: A Conceptual Analysis - Brief, Arthur P.; Rude, Dale E. (Academy of Management Review, 1981)
Facets of job satisfaction have been considered as direct predictors of voting in union certification elections in most previous research, but the relationship between satisfaction and voting is more complex. Our model of union certification voting behavior, based on Fishbein's [1967] theory of behavioral intentions, predicts that employees' attitudes toward voting for a union are influenced by their satisfaction with the economic facets of their jobs. Employees' general subjective norms toward unions are influenced by perceived expectations of the supervisor and co-workers, and by individual characteristics.